Supply chain network design under uncertain demand: robust and stable optimisation approaches. (2017) - Zanoni, Simone; Ferretti, Ivan; Mazzoldi, Laura
This paper is focused on the design of a supply chain taking into account the variability of the final customer demand: the traditional strategy for the network configurations so as to face such uncertainty, named robust approach, to seek the minimum expected total cost over the planning horizon. The novelty of this contribution resides in the investigation of an alternative way to face the uncertainty, named stable approach, which aim is to determine the minimum variability of transport and handling cost in the considered time horizon. The goal is the definition of the network configuration that can efficiently operate under the uncertainty of the customer demand, to this extent the solutions of the robust and the stable approaches have been compared. A numerical analysis has been performed over a realistic case study data and results of robust and stable and hybrid solutions have been reported.